PTU-193 Wide variation in the use of radiotherapy in the management of surgically treated rectal cancer across the english NHS. (22nd June 2015) - Morris, EJA; Finan, PJ; Quirke, PT; Thomas, JD; Spencer, K; Lawton, S; Adams, R; Sebag-Montefiore, D
Abstract : Introduction: Radiotherapy is an important treatment modality in the multidisciplinary management of rectal cancer. It is delivered both in the neo-adjuvant setting and postoperatively but, whilst it reduces local recurrence, it does not influence overall survival and increases the risk of long-term complications. This has led to a variety of international practice patterns. This variation can have significant impact on commissioning but also future clinical research. This study explores its use within the large English National Health Service (NHS). Method: Information on all individuals diagnosed with a surgically treated rectal cancer between the April 2009 and December 2010 were extracted from the Radiotherapy Dataset (RTDS) linked to the National Cancer Data Repository (NCDR). Individuals were grouped into those receiving no radiotherapy (NRT), short-course radiotherapy with immediate surgery (SCRT-I), short-course radiotherapy with delayed surgery (SCRT-D), long-course chemoradiotherapy (LCCRT), other radiotherapy (ORT) and post-operative radiotherapy (PORT). Patterns of use were then investigated. Results: The study consisted of 9, 201 individuals; 4, 538 (49.3%) received some form of radiotherapy. SCRT-I was used in 12.3%, SCRT-D in 3.7%, LCCRT in 26.5%, ORT in 5.0% and PORT in 2.2%. Radiotherapy was used more commonly in men and in those receiving abdominoperineal excision and less commonly in the elderly and those with co-morbidity. Significant and substantial variations were also seen in its use across all the multidisciplinary teams managing this disease with the proportion of any radiotherapy use ranging from 5.1% to 77.8% of surgically treated rectal cancer patients treated in each of the MDTs managing the disease across England. Conclusion: Wide variation exists in both the use of and type of radiotherapy delivered in the management of rectal cancer across the English NHS. Prospective population-based collection of local recurrence and patient-reported late toxicity information are required to further improve patient selection for preoperative radiotherapy. Disclosure of interest: None Declared.